Initial co-ideation phase of a shared decision-making tool aimed at promoting physical activity in primary care: views expressed by patients, academics, and healthcare professionals - Ramirez-Duran, Maria Valle; Prieto-López, Lola; Antón-Rodríguez, Cristina; García-Ramos, Andrés; Monge-Martín, Diana; Gómez-Salgado, Juan; Coronado-Vázquez, Valle (Frontiers in Public Health, 2025)
IntroductionAlthough physical activity is a key determinant of health, it is not yet sufficiently promoted in primary care due to communication barriers and a lack of decision-making tools tailored to patients’ preferences.ObjectivesThe aim of this study was to explore the views, needs, and expectations of patients, academics, and healthcare professionals regarding physical activity and shared decision-making in primary care, as part of the initial phase of co-ideation for the development of a shared decision-making tool.MethodsThis was a qualitative study based on focus groups. Participants were selected through purposive sampling to ensure representation of patients, academics, and healthcare professionals. Data were collected between June and December 2023 using a semi-structured interview guide. All focus groups were audio-recorded, transcribed verbatim, and analysed thematically using NVivo software.ResultsTwo topics emerged: (1) Perceptions of sedentary lifestyles and healthy physical activity, and (2) Views on a shared decision-making tool to promote healthy physical activity. Within the first topic, four categories emerged: Conceptions of sedentary lifestyle and healthy physical activity; Misconception of everyday activities as non-exercise; Exercise preferences and habits; and Barriers to exercise. Within the second topic, four other categories emerged: Functional value of SDM tools: personalisation, relevance, and shared responsibility; Collaborative dynamics between patients and professionals; Structural and relational barriers to shared decision-making such as time constraints in consultations and lack of training in motivational communication and Implementation difficulties related to digital literacy and access; Tailoring SDM tools: personalisation, inclusivity, and real-life applicability such simplifying the language, co-designing the tool with patients, and integrating it into routine clinical workflows were the recommended strategies to facilitate adoption.ConclusionThis initial co-ideation process revealed key user preferences and implementation challenges that should be considered when developing a shared decision-making tool for promoting physical activity in primary care. These findings highlight the importance of involving patients, professionals, and academics in the early stages of the design of the tool to improve its usability, acceptability, and impact on clinical practice.